2015
DOI: 10.1362/147539215x14373846805743
|View full text |Cite
|
Sign up to set email alerts
|

An old model for a new age: Consumer decision making in participatory digital culture

Abstract: Both the trade press and academic research document the shift in consumption practices instigated by the rise of web-based 'participatory culture' where each user can be a producer, influencer and/or consumer of information (Han, 2011;Jenkins, 1992). Naturally, a growing stream of research is busy re-evaluating the applicability of long-established models and constructs in this new digital reality (Abstract The Engel, Kollatt, & Blackwell (EKB) decision-making model has long been a core theory of consumer beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 40 publications
(63 reference statements)
1
53
0
2
Order By: Relevance
“…Social media has brought on a 'participatory culture' where users network with other like-minded individuals to engage in an unending loop of sharing information, monitoring updates, and requesting opinions and ratings on all kinds of products, services and activities (Ashman et al, 2015). The quality of online product reviews, characterised by perceived informativeness and persuasiveness, together with the perceived quantity of reviews, are found to have a significant positive influence on consumers' purchase intentions (Zhou et al, 2013;Zhang et al, 2014).…”
Section: Impact Of Social Media On Consumer Decisionsmentioning
confidence: 99%
“…Social media has brought on a 'participatory culture' where users network with other like-minded individuals to engage in an unending loop of sharing information, monitoring updates, and requesting opinions and ratings on all kinds of products, services and activities (Ashman et al, 2015). The quality of online product reviews, characterised by perceived informativeness and persuasiveness, together with the perceived quantity of reviews, are found to have a significant positive influence on consumers' purchase intentions (Zhou et al, 2013;Zhang et al, 2014).…”
Section: Impact Of Social Media On Consumer Decisionsmentioning
confidence: 99%
“…For sustainable business success, the service providers have the capability to predict consumer changing pattern properly for making the proper marketing strategy in the digital market (Ashman et al, 2015;Erevelles et al, 2016). This study has narrowed down this literature gap and developed a structural hierarchy model of factors, which are responsible for the changing pattern of consumer decision making in digital market as presented in Fig.4.…”
Section: Implications To Theory and Practicementioning
confidence: 99%
“…The trendiest productsAkhter et al (2005);Ashman et al (2015); Khare(2 2. Varieties of productsAshman et al (2015);Barrows and Ollivier (2018 Kumar andDash (2015); Mittelman et al (2017) 3. Standard and expectations for a product Kim et al (2010); Pappas (2016); Rezaei et al (201 4.…”
mentioning
confidence: 99%
“…The much less complex and therefore lower involvement decision to purchase a bottle of milk would not be expected to require such a journey. Ashman, Solomon and Wolny (2015) have called for empirical research which considers the degree of involvement associated with the purchase and the CJM model could be tested accordingly. (Tamsin Scott, 2015) The following apocryphal account (Deciding where to take a city-break) is apposite in this context because although it is imaginary it is illustrative of how a high-involvement decision to take an international city break might be made.…”
Section: The Customer Journeymentioning
confidence: 99%